Landform recognition in granite mountains in East Asia (Seoraksan, Republic of Korea, and Huangshan and Sanqingshan - Piotr, Migoń; Kyung-Sik, Woo; Kasprzak, Marek (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2018)
Applied research in geomorphology includes landform analysis and evaluation from a specific perspective of scientific significance and global relevance. In this paper, landform diversity of Seoraksan, Republic of Korea, a UNESCO World Heritage candidate, is compared with geomorphic characteristics of two World Heritage properties in China, Huangshan and Sanqingshan. Seoraksan represents an almost complete mountain geomorphic system of considerable contemporary dynamics, with outstanding scenery and spectacular landforms such as domes, fins, bedrock channels, waterfalls, and inherited block fields. It is argued that Seoraksan contains outstanding scientific and aesthetic values, not present at the Chinese properties, offering scope for successful nomination.
Keywords: granite geomorphology; rock control; mass movements; bedrock channels; World Heritage